2016
DOI: 10.1016/j.msea.2016.03.096
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of Portevin-Le Chatelier plastic instabilities in carbon-manganese steels by infrared pyrometry

Abstract: The dynamic strain aging (DSA) phenomenon that occurs in some materials under certain temperature and strain rate conditions can cause plastic strain localization in the form of Portevin-Le Chatelier (PLC) bands. Carbon-manganese steels are used commonly and frequently in construction because of their ductility, low cost and ability to form mechanically. In these steels, the DSA phenomenon occurs for common quasi-static strain rates from 150 to 300°C, which makes band observation complicated. PLC bands on a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…This effect is called negative strain rate sensitivity (NSRS). The main factors causing the NSRS are the DSA suppression by an increment in dislocations velocity and the inhibition of deformation twinning under high strain rates [8,9].…”
Section: The Nature Of Plc Effect In Steelsmentioning
confidence: 99%
See 4 more Smart Citations
“…This effect is called negative strain rate sensitivity (NSRS). The main factors causing the NSRS are the DSA suppression by an increment in dislocations velocity and the inhibition of deformation twinning under high strain rates [8,9].…”
Section: The Nature Of Plc Effect In Steelsmentioning
confidence: 99%
“…Several authors reported that the NSRS effect is related to the stability of RA due to adiabatic heating at high strain rates. Generally, adiabatic heating affects both the DSA and NSRS by increased diffusion intensity [8,9,15,49]. Callahan et al [52] reported that the NSRS in 0.2C-5Mn-2.5Al TRIP steel is due to the effect of adiabatic heating, which increases the stability of retained austenite, and thus reduces the work hardening rate.…”
Section: Effect Of Strain Rate On the Plc Effectmentioning
confidence: 99%
See 3 more Smart Citations